Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Pemerintah Daerah Kota Pasuruan - Alief Faza Anugerah; Hero Priono (Jurnal Akuntan Publik, 2023)
This study aims to analyze and determine the effect of Regional Original Income (PAD), Regional Expenditure and Regional Financing on the Economic Growth of the Regional Government of Pasuruan City. This study uses a quantitative approach. The sample method used is the Saturated Sampling method. The data used in this study is secondary data consisting of Economic Growth in Pasuruan City, the data obtained from the Pasuruan City BPS website and Budget Realization Report data obtained from the official website of Pasuruan City. Analysis of the data used in this research uses multiple linear analysis which is processed using the SPSS application. The results of this study show that partially there is no influence between Regional Original Income (PAD), Regional Expenditures, and Regional Financing on the Economic Growth of Pasuruan City.